Confession: A Way for the Weak to Live Courageously in Truth – A Philosophical Approach - Lichacz, Piotr (Przegląd Tomistyczny, 2025)
This paper is a philosophical reflection based on Thomas Aquinas’s texts on the value of admitting one’s failures to oneself and confessing them to others. Under special conditions such admitting and confessing may be helpful in embracing a fragile form of courageous living in truth even with the burden of many miserable deeds. Reflecting on one’s own past, present and future can lead to an appreciation of a special habit of mind, a disposition enhancing one’s functioning, even a virtue of deploring reasonably one’s moral failures. It can be called virtue of penance — a virtue of living in truth with one’s lamentable past